Levels of Leadership Characteristics of Educational Personnel, Nakhon Ratchasima College of Agriculture and Technology - Monritthanupap, Sittisak; Reenwilairat, Wichan; Kumhom, Naitawan (RATANABUTH JOURNAL, 2022)
The objectives of this research were 1) Levels of leadership characteristics of educational personnel, 2) Volunteer level of educational personnel, and 3) Relationship of Leadership Characteristics to Volunteering in School Management of Educational Personnel Nakhon Ratchasima College of Agriculture and Technology, Sikhio District, Nakhon Ratchasima Province. The population used in the research consisted of 57 people. The research instruments were questionnaires, statistical data analysis, percentage, mean, standard deviation.and Pearson correlation coefficient. The results of the research showed that 1) Levels of leadership characteristics of educational personnel Nakhon Ratchasima College of Agriculture and Technology, Sikhio District, Nakhon Ratchasima Province Has the highest democratic leadership. 2) Volunteer level of educational personnel Nakhon Ratchasima College of Agriculture and Technology, Sikhio District, Nakhon Ratchasima Province found that teachers and educational personnel Most of Nakhon Ratchasima College of Agriculture and Technology had 39 volunteers. followed by 16 volunteers, and 2 moderate volunteers. 3) Relationship of Leadership Characteristics and Volunteer Spirit in School Management of Educational Personnel Nakhon Ratchasima College of Agriculture and Technology, Sikhio District, Nakhon Ratchasima Province Low correlation.